Comparison of Bacterial Contamination in Sea Turtle Natural and Semi-natural Hatching Nest at Boom Beach Banyuwangi - Ratih Novita Praja; Aditya Yudhana; Wiyanto Haditanojo; Didik Handijatno; Muhammad Thohawi Elziyad Purnama; Salipudin Tasil Maslamama; Alivia Khairina Insani; Dhenatra Rifqy Prasetyo; Nindya Pradnya Prameswari; Shifa Salsabilla Praja (The Indian Veterinary Journal, 2024)
This study aims to investigate the total number of bacterial contamination in sea turtle natural hatching nest and semi-natural hatching nest. Sand samples were taken from sea turtle natural and semi-natural hatching nest located where at Boom beach, Banyuwangi, East Java Province, Indonesia. Total Plate Count (TPC) method was used in this study. The results show a total of 2,9 x 106 colonies were detected from natural hatching nest, while a total of 2,3 x 106 bacterial colonies were detected from semi-natural hatching nest. This research concluded that bacterial colonies were obtained from natural and semi-natural hatching nests. Furthermore, further studies need to be carried out regarding the isolation of specific bacteria using culture media to determine the species of pathogenic bacteria that have the potential to reduce the success of turtle egg hatching.